MEKANISME PASAR MODAL ATAU PERDAGANGAN EFEK SYARIAH (FATWA DSN-MUI) - Nurhaeti, Nurhaeti; Nasrulloh, Deka Ahmad (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
In national economic development, the capital market has a strategic role, namely as a source of long-term financing for the business world and an investment vehicle for investors. The problem in the Islamic capital market is that regulations, mechanisms and market transactions as a whole have elements that are prohibited by Islam. Overall, the trading mechanism on the Indonesia Stock Exchange based on the DSN-MUI Fatwa has been well implemented. This can be seen from the indicators of sharia securities issuance criteria, securities trading mechanisms, prohibited types and transactions, and sharia securities. still has a shortcoming, namely the lack of information provided by the broker so that customers get incorrect information such as regarding fees and contracts made more likely to be intended for brokers (companies).Keywords : Mechanism, Sharia Securities Trading, Fatwa DSN-MUI